2006
DOI: 10.2164/jandrol.106.000703
|View full text |Cite
|
Sign up to set email alerts
|

Protamine Levels Vary Between Individual Sperm Cells of Infertile Human Males and Correlate With Viability and DNA Integrity

Abstract: Sperm protamine deficiency has been associated with human male infertility. However, most studies have adopted a global approach to assessing sperm protamine levels. Thus, it is not known whether sperm cells from individual human males possess variations in protamine protein content. The objectives of this study were to evaluate variations in protamine-1 (P1) and protamine-2 (P2) content between individual sperm cells of fertile and infertile men and to correlate DNA integrity and sperm cell viability with pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(128 citation statements)
references
References 27 publications
(50 reference statements)
9
115
0
4
Order By: Relevance
“…The indirect association between abnormal protamine expression and severely altered spermatogenesis may not be intuitively obvious, but animal studies have also shown that spermatogenesis is severely altered when protamine expression is experimentally reduced [Zhong et al 1999;Aoki et al 2005]. In contrast to human data, haploinsufficient mice show a homogenous population of severely affected sperm, while infertile male patients with protamine deregulation exhibit a truly heterogenous population of sperm [Cho et al 2001;Aoki et al 2005;Aoki et al 2006b;Zhang et al 2006]. This may be due to focal disruptions in the tubular structure of the testis or disruption of upstream regulators with an incomplete phenotypic penetrance.…”
Section: Discussionmentioning
confidence: 99%
“…The indirect association between abnormal protamine expression and severely altered spermatogenesis may not be intuitively obvious, but animal studies have also shown that spermatogenesis is severely altered when protamine expression is experimentally reduced [Zhong et al 1999;Aoki et al 2005]. In contrast to human data, haploinsufficient mice show a homogenous population of severely affected sperm, while infertile male patients with protamine deregulation exhibit a truly heterogenous population of sperm [Cho et al 2001;Aoki et al 2005;Aoki et al 2006b;Zhang et al 2006]. This may be due to focal disruptions in the tubular structure of the testis or disruption of upstream regulators with an incomplete phenotypic penetrance.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the PRM1 and PRM2 genes have been identified in infertile men [Aoki et al 2006b;Ravel et al 2007]. Lower expression of one or both genes is associated with severe male infertility and also DNA damage in spermatozoa as evidenced by acridine orange staining [Aoki et al 2006a;Cho et al 2003]. Defects in the regulation of expression of protamines have been observed in infertile men as premature expression or retention of mRNA leads to infertility [Aoki et al 2006b;Lee et al 1995].…”
Section: Protaminesmentioning
confidence: 99%
“…gonadotoxins, hyperthermia, oxidants, endocrine abnormalities) [2][3][4][5][6][7][8][9][10]. Investigators have suggested that protamine deficiency (with aberrant chromatin remodeling), reactive oxygen species (ROS) and abortive apoptosis may cause sperm DNA damage [11][12][13][14][15][16][17][18]. De Iuliis et al, have proposed a two-step model to explain the origin of sperm DNA damage.…”
Section: Introductionmentioning
confidence: 99%